Sub-elite sprinters and rugby players possess different morphological characteristics of the individual hamstrings and quadriceps muscles - Kawama, R.; Okudaira, M.; Shimasaki, T.; Maemura, H.; Tanigawa, S. (PLOS ONE, 2021)
Numerous studies have clarified that sprinters possess unique morphological characteristics of the thigh muscles compared with non-athletes. However, little evidence is available regarding the morphological differences between sprinters and rugby players. This study aimed to examine the morphological differences in the individual hamstrings and quadriceps femoris muscles between sub-elite sprinters and rugby players. Ultrasound images were acquired from the proximal, middle, and distal regions of the thigh. From the images, the anatomical cross-sectional areas were calculated for 14 sub-elite sprinters, 14 rugby players, and 14 non-athletes. The calculated anatomical cross-sectional areas were normalized to two-thirds power of the body mass, and the normalized values of all regions were averaged as those of the individual muscles. In the hamstrings, the sizes of the biceps femoris short head and semitendinosus were greater in the sprinters than in the rugby players and/or non-athletes (all p < 0.05). In contrast, in the quadriceps femoris, the sizes of the rectus femoris, vastus lateralis, and vastus intermedius were the greatest in the rugby players (all p < 0.05). In the middle region of the biceps femoris short head and the proximal-middle regions of the semitendinosus, the muscle sizes were greater in the sprinters than in the rugby players (all p < 0.05), and vice versa in the middle-distal regions of the rectus femoris (all p < 0.05). These results suggest that 1) sub-elite sprinters possess larger sizes of the biceps femoris short head and semitendinosus, whereas rugby players have larger sizes of the rectus femoris, vastus lateralis, and vastus intermedius, and 2) each of the athletes has different size distributions, especially along the lengths of BFsh, ST, and RF. The findings of the present study would be helpful for rugby players in designing training regimens aimed at enhancing sprint performance.